Global pension challenges : pensions, saving and retirement in the twenty-first century - Ring, Patrick; Lowe, Jonquil; Luu, Liên, 1967- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"National pension systems face a range of tough social and economic demands and pressures. These are complex to navigate, especially in a twenty-first century that has ushered in global uncertainty and pressing challenges - even threatening the planet's very sustainability - with implications for pensions that policymakers, financial services providers and individuals themselves must address. This book probes, and unpacks, what pension systems aim to achieve, the uncertainties they face and how they are attempting to resolve them. Analysing pension provision from the systemic, political-economy and personal perspectives, it sets out and contextualises commonalities and differences in pension systems across the globe, looking at current developments in both public and private pension provision, structures and regulation. Moreover, the reader is encouraged to question how national pension systems can best serve their populations and ensure the 'sustainability' of later-life incomes in the light of today's global pension challenges. Global Pension Challenges is an essential read for business, finance and social-policy academics and students, those working in the pensions industry and in the areas of welfare reform and advocacy, as well as the general public wishing to know more about the retirement issues that we will all face in the coming years"--
The retirement challenge / Jonquil Lowe -- The state and pensions / Jonquil Lowe -- Risk and private pension provision / Patrick J. Ring -- Individuals and the retirement challenge / Lien Luu -- Empowering savers: saving for retirement and government policies / Lien Luu.
Keywords: Pensions; Retirement income -- Planning; BUSINESS & ECONOMICS / Personal Finance / Retirement Planning; BUSINESS & ECONOMICS / Investments & Securities